2018
DOI: 10.1007/s10639-018-9776-5
|View full text |Cite
|
Sign up to set email alerts
|

Understanding student use of twitter and online forums in higher education

Abstract: The aim of this study was to better understand how students use online forums and Twitter in undergraduate learning. Students completed an anonymous online survey (N = 50, 54% completion rate) to assess their general approach to these tools, the types of interaction experienced and specific uses. Students were also asked to relate their use to categories of learning outcomes and rate the importance of different factors in using each tool. The study demonstrates more students use forums than Twitter but that bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 14 publications
1
11
0
11
Order By: Relevance
“…They generally stated that Twitter helped to improve their writing and their views about writing. This finding is similar to those of many studies that show evidence of Twitter's utility in language learning and specifically writing (Altakhaineh & Al-Jallad, 2018;Ammar, 2016;Dommett, 2019;Kartal & Korucu-Kis, 2020;Mompean & Fouz-González, 2016;Wu, 2020).…”
Section: The Students' Views About the Use Of Twitter In Their Writinsupporting
confidence: 89%
See 1 more Smart Citation
“…They generally stated that Twitter helped to improve their writing and their views about writing. This finding is similar to those of many studies that show evidence of Twitter's utility in language learning and specifically writing (Altakhaineh & Al-Jallad, 2018;Ammar, 2016;Dommett, 2019;Kartal & Korucu-Kis, 2020;Mompean & Fouz-González, 2016;Wu, 2020).…”
Section: The Students' Views About the Use Of Twitter In Their Writinsupporting
confidence: 89%
“…One possible strategy is to integrate technology in their curricula, such as social media tools and applications, which allow students to write for a larger audience and take responsibility for their writing (Morgan, 2014;Nasrullah & Khan, 2019). The integration of technology is not without its drawbacks (Dommett, 2019). Nevertheless, this exploratory study attempted to investigate these issues in a new context.…”
Section: Introductionmentioning
confidence: 99%
“…La incorporación de esta red social en Educación Superior ha sido objeto de muchos estudios en la literatura especializada, entre los que destacan los de Grosseck y Holotescu (2008), que señalan el potencial educativo que esta red social proporciona al favorecer el desarrollo de las habilidades de síntesis de la información en un contexto de interacción inmediata. Otros autores como Thoms y Eryilmaz (2015) o Htay et al (2020), indican que este tipo de herramientas fomenta el aprendizaje autónomo de los estudiantes, convirtiéndolos en auténticos protagonistas del hecho educati-vo, potenciando el aprendizaje informal (Tess, 2013;Dommett, 2019), facilitando las interacciones sociales de todos los implicados desde el trabajo colaborativo (García-Suárez et al, 2015;Fernández-Ferrer & Cano, 2019;Malik et al, 2019) y fomentando la integración de nuevas metodologías en Educación Superior.…”
Section: Las Redes Sociales Como Recurso Metodológico: El Caso De Twiunclassified
“…Students are concerned about the extra workload imposed by Seven studies focused on prevalence of using a particular application in collaborative online learning. Studies found that collaborative online learning applications are useful for knowledge acquisition (29,30).…”
Section: • Learning Designmentioning
confidence: 99%